The moral rebel: measurement, correlates, and perceptions - Sonnentag, Tammy L. (Kansas State University, 2010)
The term “moral rebel” describes an individual who refuses to comply, remain silent, or conform to others when doing so would compromise his or her values. Although researchers have identified individuals whose moral judgments reflect an adherence to “individual principles and conscience,” little attention has been given to the assessment, correlates, and perceptions of individuals who follow their own moral convictions despite considerable social pressure not to do so. The present study examined (1) the extent to which adolescents, peers, and teachers agree in their ratings of adolescents’ tendencies to be a moral rebel, (2) some characteristics potentially associated with differences in adolescents’ tendencies to be a moral rebel, and (3) the extent to which adolescents’ attitudes toward a moral rebel (vs. a non-moral rebel) are influenced by their own level of “moral rebelness” (as assessed by self, peers, and teachers). Results revealed significant positive correlations among all of the self-report, peer, and teacher ratings of moral rebelness for the entire sample (and for male and female participants considered separately). Contrary to predictions, self-report, peer and teacher ratings of adolescents’ moral rebelness were not robustly associated with any individual difference variable. Generally, adolescents reported relatively favorable attitudes toward a moral rebel (compared to a non-moral rebel), especially when they themselves had heightened ratings on this characteristic. The implications and limitations of the present findings, as well as directions for future research on the topic of moral rebelness in adolescents, are addressed.
Keywords: Moral Rebel; Psychology, Developmental (0620); Psychology, Personality (0625); Psychology, Social (0451)